Ketuntasan Belajar Siswa Pada Mata Pelajaran PAI Melalui Metode Kisah - Kuswoyo, Pandi (Jurnal Pendidikan Islam, 2012)
This study aims to improve the mastery of learning through the application of methods of stories on the subjects of Islamic religious education aspects of morality. This is a classroom action research that is carried out in three cycles. The cycle 1, the average of the student learning achievement values reached 82 with the completeness of 86%. Cycle 2, the average of the student learning achievement values reached 91.79 with the completeness of 92%.While on cycle 3, the average of the student learning achievement values reached 92.14 with the completeness of 96%. In Addition, Increased activity of teachers in the learning process also tends to increase of the cycle I reached 63.6%, the second cycle Increased to 85.5%, and 96.4%.